High‐Efficiency FRET Processes in BODIPY‐Functionalized Quantum Dot Architectures. Issue 7 (23rd December 2020) - Panniello, Annamaria; Trapani, Mariachiara; Cordaro, Massimiliano; Dibenedetto, Carlo Nazareno; Tommasi, Raffaele; Ingrosso, Chiara; Fanizza, Elisabetta; Grisorio, Roberto; Collini, Elisabetta; Agostiano, Angela; Curri, Maria Lucia; Castriciano, Maria Angela; et al.
Abstract: Efficient FRET systems are developed combining colloidal CdSe quantum dots (QDs) donors and BODIPY acceptors. To promote effective energy transfer in FRET architectures, the distance between the organic fluorophore and the QDs needs to be optimized by a careful system engineering. In this context, BODIPY dyes bearing amino‐terminated functionalities are used in virtue of the high affinity of amine groups in coordinating the QD surface. A preliminary QD surface treatment with a short amine ligand is performed to favor the interaction with the organic fluorophores in solution. The successful coordination of the dye to the QD surface, accomplishing a short donor–acceptor distance, provides effective energy transfer already in solution, with efficiency of 76 %. The efficiency further increases in the solid state where the QDs and the dye are deposited as single coordinated units from solution, with a distance between the fluorophores down to 2.2 nm, demonstrating the effectiveness of the coupling strategy. Abstract : Fabrication of FRET platforms, formed by colloidal CdSe QDs and fluorescent BODIPY dyes. The successful functionalization of the QD surface by the dye allows to obtain very short distances and high FRET efficiency, both in solution and in the solid state, where the donor and acceptor are deposited in single coupled units.